EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MAHASISWA MATA KULIAH KALKULUS PEUBAH BANYAK - Sri Wahyuni (MES: Journal of Mathematics Education and Science, 2018)
Abstract. Student activity will affect effectiveness for student learning outcomes. The effectiveness of learning consists of four indicators, namely the quality of instruction, the suitability appropriate level of instruction, incentive, and time. The purpose of this study is to: (1) Know how the effectiveness of student learning outcomes in variable calculus subjects after getting learning with discovery learning learning models. (2) Knowing whether there is an increase in student learning outcomes in many variable calculus subjects after getting learning with discovery learning learning models. The data analysis techniques are carried out from the data description test stage, then the prerequisite test is the normality and linearity test, then test the hypothesis. The steps in the study are as follows: (1) The researcher provides a stimulus for the sample class, namely the discovery learning model; (2) At the time of the learning process the partner lecturers see the activity, student learning; (3) Provide essay tests to see the level of success of students in learning; (4) Perform statistical tests to see the effectiveness of student learning outcomes using discovery learning learning models. The results of this study are that there is an effect on the effectiveness of mathematics learning using the discovery learning model of student learning outcomes in many variable calculus subjects, and there is an increase in student learning outcomes after learning with discovery learning models of many variable calculus subjects as much as 20.53.Keywords: Discovery Learning, Learning Outcomes, Calculus